Further contributions on the description of the nest, eggs and nesting habitat of the Mexican micro-endemic and near threatened Rose-bellied Bunting (Passerina rositae) - Monroy-Ojeda, Alan; Grosselet, Manuel; Ruiz, Georgita (Huitzil Revista Mexicana de Ornitología, 2013)
While assessing species density, abundance, and distribution through transects and point counts for the near threatened species Rose-bellied Bunting, Passerina rositae, we found two active nests on two hillsides characterized by tropical dry deciduous forest on the western slope of its restricted range in the Sierra Tolistoque, in the Isthmus of Tehuantepec, Oaxaca, Mexico. In both cases, we found no evidence of human disturbance and no proximate trail systems. This description adds further details of previous nest descriptions. These new findings have conservation implications due to the fact that original habitat degradation is rapidly occurring, not only due to cattle pastures, croplands, orchards, and human settlements, but also to a fast growing wind farm and highway development projects in the region.